Structure of Excitatory Synapses and GABA(A) Receptor Localization at Inhibitory Synapses Are Regulated by Neuroplastin-65 - Herrera-Molina, Rodrigo (American Society for Biochemistry and Molecular Biology, 2014)
Formation, maintenance, and activity of excitatory and inhibitory synapses are essential for neuronal network function. Cell adhesion molecules (CAMs) are crucially involved in these processes. The CAM neuroplastin-65 (Np65) highly expressed during periods of synapse formation and stabilization is present at the pre- and postsynaptic membranes. Np65 can translocate into synapses in response to electrical stimulation and it interacts with subtypes of GABA(A) receptors in inhibitory synapses. Here, we report that in the murine hippocampus and in hippocampal primary culture, neurons of the CA1 region and the dentate gyrus (DG) express high Np65 levels, whereas expression in CA3 neurons is lower. In neuroplastin-deficient (Np(−/−)) mice the number of excitatory synapses in CA1 and DG, but not CA3 regions is reduced. Notably this picture is mirrored in mature Np(−/−) hippocampal cultures or in mature CA1 and DG wild-type (Np(+/+)) neurons treated with a function-blocking recombinant Np65-Fc extracellular fragment. Although the number of GABAergic synapses was unchanged in Np(−/−) neurons or in mature Np65-Fc-treated Np(+/+) neurons, the ratio of excitatory to inhibitory synapses was significantly lower in Np(−/−) cultures. Furthermore, GABA(A) receptor composition was altered at inhibitory synapses in Np(−/−) neurons as the α1 to α2 GABA(A) receptor subunit ratio was increased. Changes of excitatory and inhibitory synaptic function in Np(−/−) neurons were confirmed evaluating the presynaptic release function and using patch clamp recording. These data demonstrate that Np65 is an important regulator of the number and function of synapses in the hippocampus.